The Empowerment Strategy for Indonesian Fishermen to be Willing and Financially Able to Go to Sea in Zone 711 - Albert Barita Marulam Sihombing, Marsetio, Angel Damayanti, Sari Wahyuni, Hendra Manurung (Journal of International Crisis and Risk Communication Research, 2024)
The issue of empowering Indonesian fishermen is a transnational issue in the Southeast Asia regions, and Zone 711 in particular. The fisheries management area of the Republic of Indonesia 711, known as WPPNRI 711, is a water area with abundant natural resources, including oil and gas wealth and fish barns. This research is aimed at finding out how cooperation patterns work in the Fisheries Management Area of the Republic of Indonesia, from now on referred to as WPP-NRI, which is a fisheries management area for fishing that includes inland waters, archipelagic waters, territorial seas, additional zones, and Indonesia's exclusive economic zone. This research utilizes a qualitative research method using a descriptive-qualitative approach. The method of data gathering was collected using documentation studies and literature studies through Indonesian official documents such as Ministry of Maritime Affairs and Fisheries (KKP) and ASEAN as a regional international, and journal articles. Efforts to empower fishermen continuously in Indonesia, especially in the Fisheries Management Area Zone of the Republic of Indonesia (WPP-NRI) 711, are strategic decisions to optimize the local people's welfare and economic independence of coastal communities. This zone encompasses the waters of the Natuna Sea, North Natuna Sea, and Karimata Strait, which have significant fish resource potential. This research revealed and explained patterns of cooperation between KKP and ASEAN identifying the results, that many small fishermen live in poverty and face various challenges in going to sea of Zone 711. The challenges in fisheries activities are also changing weather due to uncertain seasons and increasingly distant fishing areas. Therefore, in facing these challenges, innovation, and creativity in strategic decision-making are needed by the related stakeholders to continue in providing additional economic value.